2014
DOI: 10.1007/s00198-014-2768-4
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of myasthenia gravis by alendronate

Abstract: Myasthenia gravis is an important indication for the long-term prescription of corticosteroids. We present a patient with myasthenia gravis who had worsening of symptoms associated with the use of alendronate. A 24-year-old patient with myasthenia gravis had been administered oral systemic corticosteroid (deflazacort 40 mg/day) for 3 years in order to control his myasthenic symptoms. One year earlier, his lumbar spine bone mineral density was decreased. He was started on oral calcium/vitamin D3 and alendronate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In MG, the use of oral alendronate (70 mg/week) in a patient under GC treatment improved the LS BMD of 3.4% after 12 months without side effects (103). However, caution should be paid for possible exacerbation of MG symptoms, such as muscle weakness and extreme fatigue, after drug administration (104).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…In MG, the use of oral alendronate (70 mg/week) in a patient under GC treatment improved the LS BMD of 3.4% after 12 months without side effects (103). However, caution should be paid for possible exacerbation of MG symptoms, such as muscle weakness and extreme fatigue, after drug administration (104).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…In addition, PRP has been shown to be safe with infection rates similar to that of controls. 351 However, these results need to be taken with caution as several, if not an equal number of studies have shown no significant pain relief, 352 quality of life and range of motion, 352,353 re-tear rates, [354][355][356] shoulder scores, 348,352,[354][355][356][357][358] or MRI analyses, 348,354,355,357,358 with the administration of PRPs. In addition, two meta-analyses on human trials for rotator cuff regeneration have shown no significance in terms of re-tear rates, strength regain and other clinical outcomes with PRP administration.…”
Section: Platelet-[rich Plasmamentioning
confidence: 99%
“…These antiresorptive drugs, including bisphosphonates, strontium ranelate, and estrogen, are effective inhibitors of osteoclastic bone resorption [Brewer et al, ]. Unfortunately, long‐term treatment can induce serious side effects, such as acute influenza‐like illness, myasthenia gravis, and gastrointestinal cancer [Kesikburun et al, ; Jung et al, ]. Hence, new agents are required for reducing the risk of osteoporosis and osteoporotic fractures.…”
mentioning
confidence: 99%